2014
DOI: 10.1002/cssc.201402850
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Acceptorless Alkane Dehydrogenation: Scope, Mechanism, and Conquering Deactivation with Carbon Dioxide

Abstract: Alkane dehydrogenation is of special interest for basic science but also offers interesting opportunities for industry. The existing dehydrogenation methodologies make use of heterogeneous catalysts, which suffer from harsh reaction conditions and a lack of selectivity, whereas homogeneous methodologies rely mostly on unsolicited waste generation from hydrogen acceptors. Conversely, acceptorless photochemical alkane dehydrogenation in the presence of trans-Rh(PMe3 )2 (CO)Cl can be regarded as a more benign and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
0
14
0
4
Order By: Relevance
“…Recently, work from Beller and coworkers, has resurrected the use of Vaska‐like complexes of rhodium for photochemical dehydrogenations through stabilizing the catalytically active species (Figure ). Careful study revealed that introduction of the classic chelating ligand 2,2′‐bipyridine extended the lifetime of the catalyst, permitting much increased TON for a variety of substrates.…”
Section: Dehydrogenationmentioning
confidence: 99%
“…Recently, work from Beller and coworkers, has resurrected the use of Vaska‐like complexes of rhodium for photochemical dehydrogenations through stabilizing the catalytically active species (Figure ). Careful study revealed that introduction of the classic chelating ligand 2,2′‐bipyridine extended the lifetime of the catalyst, permitting much increased TON for a variety of substrates.…”
Section: Dehydrogenationmentioning
confidence: 99%
“…Bei Bestrahlung von n ‐Octan und Katalysator in einem Schlenkgefäß mit einer Wandstärke von 1,2 mm konnten nach 7 h Katalysatorumsatzzahlen von bis zu 1518 erreicht werden. In einem weiteren Artikel von Chowdhury et al 20 konnte zudem durch die Zugabe von Ethylformiat und CO 2 eine verbesserte Stabilität des Katalysators im Reaktionssystems dokumentiert werden. Dies äußert sich in einer Verringerung der intrinsischen Katalysatordesaktivierung (Ethylformiat: TON = 2182 nach 24 h).…”
Section: Experimentelle Untersuchungenunclassified
“…Dies äußert sich in einer Verringerung der intrinsischen Katalysatordesaktivierung (Ethylformiat: TON = 2182 nach 24 h). Umfangreiche mechanistische Untersuchungen und theoretische Betrachtungen zeigten außerdem 20, dass die fotolytische Abspaltung des CO‐Liganden aus dem Komplex RhCO(PMe 3 ) 2 Cl die Reaktivität des Systems im Katalysezyklus dominiert, was mit früheren Betrachtungen von Goldman et al übereinstimmt 21, 22. Die Dehydrierung von Alkanen mit Licht im sichtbaren Bereich konnte auf Basis der Untersuchungen jedoch bis dato noch nicht realisiert werden.…”
Section: Experimentelle Untersuchungenunclassified
“…To solve these problemsm ost of the known reactions of carbon dioxide make use of highly reactive substrates and/orn eed harsh reaction conditions, limiting the practical applications of such methods. Based on our long standing interest in telomerization reactions, [28][29][30][31][32] as well as the valorization of carbon dioxide, [1,4,33] we recently started aj oint program to improvet he synthesis of the d-lactone 1 as an intermediate for novel polymers based on carbon dioxide.To develop superior catalytic systems, whicha llow for the synthesis of d-lactone 1 from 1,3-butadiene and carbon dioxide in high yield and selectivity, we studied the influenceo f variousp hosphine ligands (Scheme3;L1-L22)i nt he presence of 0.06 mol %p alladium catalyst (Pd(acac) 2 /L = 1:3). [13][14][15] In contrast to all these reactions vide supra, the catalytic telomerization of 1,3-butadiene with carbon dioxide leads straightforward to the unsaturated d-lactone 1 (3-ethylidene-6-vinyltetrahydro-2Hpyran-2-one) under mild conditions in a1 00 %a tom-efficient manner (Scheme 1).…”
mentioning
confidence: 99%
“…Based on our long standing interest in telomerization reactions, [28][29][30][31][32] as well as the valorization of carbon dioxide, [1,4,33] we recently started aj oint program to improvet he synthesis of the d-lactone 1 as an intermediate for novel polymers based on carbon dioxide. Based on our long standing interest in telomerization reactions, [28][29][30][31][32] as well as the valorization of carbon dioxide, [1,4,33] we recently started aj oint program to improvet he synthesis of the d-lactone 1 as an intermediate for novel polymers based on carbon dioxide.…”
mentioning
confidence: 99%